Synthesis, characterization, antimicrobial and electrochemical activities of zinc oxide nanoparticles obtained from sarcopoterium spinosum (L.) spach leaf extract. (7th September 2018) - Kahraman, Oskay; Binzet, Riza; Turunc, Ersan; Dogen, Aylin; Arslan, Hakan
Abstract: In this study, we introduce a green and simple method for the synthesis of ZnONPs utilizing Sarcopoterium spinosum (L.) Spach leaf extract as a reducing agent for the first time. Zinc oxide nanoparticles (ZnONPs) were synthesized with a simple, non-toxic, non-expensive and eco-friendly method. In this method, the leaf extract of S. spinosum was used as a reducing agent. Moreover, the effect of pH and calcination on the size and shape of ZnONPs were also investigated. The particle size, morphology and the electrochemical activity of the synthesized nanoparticles were characterized by using the scanning electron microscope, the UV/VIS spectroscopy, the X-ray powder diffraction, the Zeta sizer, the energy-dispersive X-ray spectroscopy and Cyclic voltammetry (CV) techniques. The synthesized ZnONPs were evaluated due to antibacterial activity against Gram-positive and Gram-negative bacteria strains and yeast. The obtained results showed that the synthesized ZnONPs show different antibacterial activity on Gram-positive and Gram-negative bacteria strains and antifungal activity against fungal strains. The reason for these different antibacterial and antifungal effects of the obtained nanoparticles is that they have various morphologies and particle sizes. Further, the cost-effective ZnONPs, obtained via biosynthesis, showed a good electroactive behavior and thus, they can be suggested as possible nominees for electrochemical applications.